Models for estimating the efficiencies of forest enterprises - Kaminskienė , Janina; Laurinavičius, Eligijus (Lietuvos matematikos rinkinys, 2004)
A data envelopment analysis (DEA) application in evaluating the efficiency is presented. The models for estimating productive and resource efficiencies of forest enterprises are used.
Keywords: data envelopment analysis; efficiency; linear programming